Mould‐reactive T cells for the diagnosis of invasive mould infection—A prospective study. Issue 7 (23rd May 2019) - Steinbach, Angela; Cornely, Oliver A.; Wisplinghoff, Hilmar; Schauss, Astrid C.; Vehreschild, Joerg J.; Rybniker, Jan; Hamprecht, Axel; Richter, Anne; Bacher, Petra; Scheffold, Alexander; Koehler, Philipp
Summary: Invasive mould infections (IMI) in immunocompromised patients are difficult to diagnose. Early and targeted treatment is paramount, but minimally invasive tests reliably identifying pathogens are lacking. We previously showed that monitoring pathogen‐specific CD4+T cells in peripheral blood using upregulation of induced CD154 positive lymphocytes can be used to diagnose acute IMI. Here, we validate our findings in an independent patient cohort. We stimulated peripheral blood cells from at‐risk patients with Aspergillus spp. and Mucorales lysates and quantitated mould‐reactive CD4/CD69/CD154 positive lymphocytes via flow cytometry. Mould‐reactive lymphocytes were quantitated in 115 at‐risk patients. In 38 (33%) patients, the test was not evaluable, mainly due to low T cell counts or non‐reactive positive control. Test results were evaluable in 77 (67%) patients. Of these, four patients (5%) had proven IMI and elevated mould‐reactive T cell signals. Of 73 (95%) patients without proven IMI, 59 (81%) had mould‐reactive T cell signals within normal range. Fourteen (19%) patients without confirmed IMI showed elevated T cell signals and 11 of those received antifungal treatment. The mould‐reactive lymphocyte assay identified presence of IMI with a sensitivity of 100% and specificity of 81%. The mould‐reactive lymphocyte assay correctly identified all patients with proven IMI. Assay applicability is limited by low T cell counts during bone marrow suppression. The assay has the potential to support diagnosis of invasive mould infection to facilitate tailored treatment even when biopsies are contraindicated or cultures remain negative.